Alectinib versus chemotherapy in crizotinib-pretreated anaplastic lymphoma kinase (ALK)-positive non-small-cell lung cancer: results from the phase III ALUR study. (14th April 2018) - Novello, S; Mazières, J; Oh, I -J; de Castro, J; Migliorino, M R; Helland, Å; Dziadziuszko, R; Griesinger, F; Kotb, A; Zeaiter, A; Cardona, A; Balas, B; et al.
Abstract: Background: This is the first trial to directly compare efficacy and safety of alectinib versus standard chemotherapy in advanced/metastatic anaplastic lymphoma kinase ( ALK )-positive non-small-cell lung cancer (NSCLC) patients who have progressed on, or were intolerant to, crizotinib. Patients and methods: ALUR (MO29750; NCT02604342) was a randomized, multicenter, open-label, phase III trial of alectinib versus chemotherapy in advanced/metastatic ALK -positive NSCLC patients previously treated with platinum-based doublet chemotherapy and crizotinib. Patients were randomized 2 : 1 to receive alectinib 600 mg twice daily or chemotherapy (pemetrexed 500 mg/m 2 or docetaxel 75 mg/m 2, both every 3 weeks) until disease progression, death, or withdrawal. Primary end point was investigator-assessed progression-free survival (PFS). Results: Altogether, 107 patients were randomized (alectinib, n = 72; chemotherapy, n = 35) in 13 countries across Europe and Asia. Median investigator-assessed PFS was 9.6 months [95% confidence interval (CI): 6.9–12.2] with alectinib and 1.4 months (95% CI: 1.3–1.6) with chemotherapy [hazard ratio (HR) 0.15 (95% CI: 0.08–0.29); P < 0.001]. Independent Review Committee-assessed PFS was also significantly longer with alectinib [HR 0.32 (95% CI: 0.17–0.59); median PFS was 7.1 months (95% CI: 6.3–10.8) with alectinib and 1.6 months (95% CI: 1.3–4.1) with chemotherapy]. In patients with measurable baseline central nervous system (CNS) disease (alectinib, n = 24; chemotherapy, n = 16), CNS objective response rate was significantly higher with alectinib (54.2%) versus chemotherapy (0%; P < 0.001). Grade ≥3 adverse events were more common with chemotherapy (41.2%) than alectinib (27.1%). Incidence of AEs leading to study-drug discontinuation was lower with alectinib (5.7%) than chemotherapy (8.8%), despite alectinib treatment duration being longer (20.1 weeks versus 6.0 weeks). Conclusion: Alectinib significantly improved systemic and CNS efficacy versus chemotherapy for crizotinib-pretreated ALK -positive NSCLC patients, with a favorable safety profile. Trial registration: ClinicalTrials.gov NCT02604342; Roche study MO29750